Case report: A kidney metastasis from vulvar squamous cell carcinoma - He, Junwei; Xiao, Yuhe; Wang, Lu; Wang, Zhaohui; Pan, Jun; Bai, Zunguang (Frontiers in Oncology, 2024)
Background: Distant metastases of vulvar SCC most commonly involve the lung, liver, bone, skin, and lymph nodes. Metastasis from vulvar SCC to the kidneys is extremely rare, with only one case reported in the literature to date. Case presentation: We report the case of a 53-year-old postmenopausal female patient was diagnosed with vulvar squamous cell carcinoma in an external hospital and following the diagnosis, she had been performed a vulvectomy for squamous cell carcinoma of the vulva，at that time, the patient had not undergone inguinal lymphadenectomy. In July 2019, she was admitted to our hospital due to upper right quadrant pain. An enhanced whole-body CT scan showed a mixed-density tumor of the right kidney with invasion into the right renal portal vein and multiple enlarged intractraperitoneal lymph nodes. Positron emission tomography-computed tomography (PET - CT) scan showed a significantly increased radioactivity uptake in the tumor and enlarged lymph nodes, but PET-CT did not show abnormal enlargement of bilateral inguinal lymph nodes and no abnormal increase in radioactivity uptake. PET-CT examination did not show recurrence in terms of local of vulvar. These results led us to be gravely worried about possible renal carcinoma, so it was agreed upon to perform laparoscopic nephrectomy of the right kidney in the same month. Histology of the resected tumor confirmed it to be poorly differentiated squamous cell carcinoma with invasion consistent with metastatic vulvar carcinoma. Based on clinical history, radiological and histological facts, the patient was diagnosed with kidney metastasis from vulvar squamous cell carcinoma. Recovery from surgery went well and the patient was transferred to the oncology department and underwent a chemotherapy regimen consisting of paclitaxel and nedaplatin for further treatment. After 6 courses of chemotherapy. For a year after treatment, the patient had lived progression-free. Unfortunately, she died of tumour progression in July 2022. Conclusions: Although renal metastasis from vulvar SCC is rare, renal metastasis should be considered for the patient with a history of vulvar cancer, whenever a mass is identified in the kidney. Timely surgical removal of renal metastasis may prolong the survival time.